Improving Marketing Skills for Traditional Market Traders - Lale Puspita Kembang; Sri Maryanti; Amiruddin Kalbuadi (Communautaire: Journal of Community Service, 2024)
This article discusses a community service program that focuses on improving marketing skills for traditional market traders to strengthen their competitiveness in modern markets. This program includes training in marketing techniques, product styling, and the use of social media for promotion. Service activities were carried out at the traditional market in Telaga Waru Village, West Lombok using observation and in-depth interview methods to evaluate the impact of the program on participating traders. The results of the service show that this training was successful in increasing traders' understanding and skills in implementing more effective marketing strategies. Significant changes can be seen in more attractive product arrangements, increased promotional activities via social media, as well as an increase in the number of customers and sales. Apart from that, this program has also succeeded in increasing traders' awareness of the importance of adapting to technological developments in marketing. The conclusion of this service emphasizes the need for continuous training and support from the government and related institutions to maintain the sustainability and competitiveness of traditional markets. Recommendations include developing more comprehensive training programs, providing access to digital resources, and collaborating with various parties to support the sustainability of this initiative.